Acute respiratory viral infections in pediatric cancer patients undergoing chemotherapy - Eliana C.A. Benites; Dayane P. Cabrini; Andrea C.B. Silva; Juliana C. Silva; Daniel T. Catalan; Eitan N. Berezin; Maria R.A. Cardoso; Saulo D. Passos (Brazilian Society of Pediatrics, 2014)
Objective: to estimate the prevalence of infection by respiratory viruses in pediatric patients with cancer and acute respiratory infection (ARI) and/or fever. Methods: cross‐sectional study, from January 2011 to December 2012. The secretions of nasopharyngeal aspirates were analyzed in children younger than 21 years with acute respiratory infections. Patients were treated at the Grupo em Defesa da Criança Com Câncer (Grendacc) and University Hospital (HU), Jundiaí, SP. The rapid test was used for detection of influenza virus (Kit Biotrin, Inc. Ireland), and real‐time multiplex polymerase chain reaction (FTD, Respiratory pathogens, multiplex Fast Trade Kit, Malta) for detection of influenza virus (H1N1, B), rhinovirus, parainfluenza virus, adenovirus, respiratory syncytial virus, human parechovirus, bocavirus, metapneumovirus, and human coronavirus. The prevalence of viral infection was estimated and association tests were used (χ2 or Fisher's exact test). Results: 104 samples of nasopharyngeal aspirate and blood were analyzed. The median age was 12 ± 5.2 years, 51% males, 68% whites, 32% had repeated ARIs, 32% prior antibiotic use, 19.8% cough, and 8% contact with ARIs. A total of 94.3% were in good general status. Acute lymphocytic leukemia (42.3%) was the most prevalent neoplasia. Respiratory viruses were detected in 50 samples: rhinoviruses (23.1%), respiratory syncytial virus AB (8.7%), and coronavirus (6.8%). Co‐detection occurred in 19% of cases with 2 viruses and in 3% of those with 3 viruses, and was more frequent between rhinovirus and coronavirus 43. Fever in neutropenic patients was observed in 13%, of which four (30.7) were positive for viruses. There were no deaths. Conclusions: the prevalence of respiratory viruses was relevant in the infectious episode, with no increase in morbidity and mortality. Viral co‐detection was frequent in patients with cancer and ARIs.